Hand hygiene--evaluation of three disinfectant hand sanitizers in a community setting. - Rita Babeluk (PLoS ONE, 2014)
Hand hygiene is acknowledged as the single most important measure to prevent nosocomial infections in the healthcare setting. Similarly, in non-clinical settings, hand hygiene is recognised as a key element in helping prevent the spread of infectious diseases. The aim of this study was to evaluate the efficacy of three different disinfectant hand sanitizers in reducing the burden of bacterial hand contamination in 60 healthy volunteers in a community setting, both before and after education about the correct use of hand sanitizers. The study is the first to evaluate the efficacy and ease of use of different formulations of hand rubs used by the general population. The products tested were: Sterillium (perfumed, liquid), desderman pure gel (odorless, gel) and Lavit (perfumed, spray). Sterillium and desderman are EN1500 (hygienic hand rub) certified products (available in pharmacy) and Lavit is non EN1500 certified and available in supermarkets. The two EN1500 certified products were found to be significantly superior in terms of reducing bacterial load. desderman pure gel, Sterillium and Lavit reduced the bacterial count to 6.4%, 8.2% and 28.0% respectively. After education in the correct use of each hand rub, the bacterial load was reduced even further, demonstrating the value of education in improving hand hygiene. Information about the testers' perceptions of the three sanitizers, together with their expectations of a hand sanitizer was obtained through a questionnaire. Efficacy, followed by skin compatibility were found to be the two most important attributes of a hand disinfectant in our target group.